2006
DOI: 10.1089/acm.2006.12.133
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical and Biologic Profile of a Red Clover (Trifolium pratense L.) Phase II Clinical Extract

Abstract: The major and minor chemical and active estrogenic components of a preformulated phase II red clover clinical extract were identified, quantitatively measured, and the final capsule doses were calculated. The extract is currently under evaluation in a year-long clinical study for the alleviation of menopausal hot flashes. This is the first report to thoroughly summarize the chemistry and biology of all major peaks observed in the HPLC-UV chromatogram of a clinical red clover dietary supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 29 publications
4
85
1
1
Order By: Relevance
“…These results suggest that a higher number of OH group substitutions on the aglycone moiety substantially affect the relative abundance of the [Y 0 − H] −• ion, resulting in higher ion abundance. When compared with compound 3, it was found that the presence of the OCH 3 of the Y 0 − ion (Fig. 4(a)).…”
Section: The Fragmentation Behavior Of Compounds 1-4mentioning
confidence: 99%
“…These results suggest that a higher number of OH group substitutions on the aglycone moiety substantially affect the relative abundance of the [Y 0 − H] −• ion, resulting in higher ion abundance. When compared with compound 3, it was found that the presence of the OCH 3 of the Y 0 − ion (Fig. 4(a)).…”
Section: The Fragmentation Behavior Of Compounds 1-4mentioning
confidence: 99%
“…The aerial parts of this plant contain at least seven additional isoflavones when compared with soybeans, which are rich in daidzein, genistein, and glycitein (Wu et al, 2003). On one hand, dietary supplements containing red clover extracts are mainly administered as an alternative to the conventional hormonal replacement therapy (Booth et al, 2006;Engelmann et al, 2009). Isoflavones (such as daidzein, genistein, biochanin A, and formononetin) display diverse biological activities, including antioxidant (Ruiz-Larrea et al, 1997), anti-inflammatory, and anti-tumor actions (Krenn & Paper, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Essa planta contém isoflavonas estrogênicas, assim como a soja, sendo as principais a biochanina proestrogênica e formononetina (BOOTH et al, 2006). Os precursores metoxi são desmetilados pelo isozimas do citocromo P450 no intestino e no fíga-do em genisteína e daidzeína seletivas para o RE (DIETZ et al, 2016) que são efetivas na perda óssea induzida por ovarectomia, provavelmente pela redução no tunover ósseo da reabsorção óssea (CIRCOSTA et al, 2006;BECK;ROHR;JUNGBAUER, 2005).…”
Section: As Plantas Medicinais Que Podem Ser Utilizadas Para Tratamenunclassified